2020
DOI: 10.1159/000512232
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Characteristics and Outcomes of COVID-19 Infections in Patients with Diabetes at a Tertiary Care Center in the UAE

Abstract: <b><i>Introduction:</i></b> Uncontrolled glycemia is a well-recognized predictor of severity and deaths in previous respiratory viral outbreaks. We aimed to describe the characteristics and clinical course of patients with diabetes admitted with COVID-19 infection at a tertiary care center in the Emirate of Dubai, UAE, and assess the impact of hyperglycemia on the clinical outcomes. <b><i>Methods:</i></b> This study is a single-center, observational, retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 17 publications
3
17
0
1
Order By: Relevance
“…Additionally, studies from London and the US said that nonwhite patients with DM were the majority among COVID-19 cohorts, with 72% and 56%, respectively [40] , [41] . Furthermore, the prevalence of DM in COVID-19 patients has been higher in adults over 50 years of age, especially in those aged 65-70 years [29] , [30] , [33] , [37] , [42] . Other studies indicate that male patients with DM had a significant prevalence (50–60%) among COVID-19 patients [31] , [42] , [43] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, studies from London and the US said that nonwhite patients with DM were the majority among COVID-19 cohorts, with 72% and 56%, respectively [40] , [41] . Furthermore, the prevalence of DM in COVID-19 patients has been higher in adults over 50 years of age, especially in those aged 65-70 years [29] , [30] , [33] , [37] , [42] . Other studies indicate that male patients with DM had a significant prevalence (50–60%) among COVID-19 patients [31] , [42] , [43] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the prevalence of DM in COVID-19 patients has been higher in adults over 50 years of age, especially in those aged 65-70 years [29] , [30] , [33] , [37] , [42] . Other studies indicate that male patients with DM had a significant prevalence (50–60%) among COVID-19 patients [31] , [42] , [43] . Unfortunately, the association of DM with COVID-19 has usually resulted in severe illness or poor prognosis [21] , [34] , [44] .…”
Section: Introductionmentioning
confidence: 99%
“…There was significant difference between sex of admitted patients, since the ratio was around 2:1 for males vs. females. But, in similar study led by Hafidh et al, the percent of males with diabetes was 94% 18 . Guo et al, also proved that diabetes was significantly more prevalent in patients who were admitted in intensive care, required mechanical ventilation, with fatal outcome, than in patients who did not have these complications (26.9% vs 6.1%) 19 .…”
Section: Discussionmentioning
confidence: 79%
“…A study from UAE found mortality of 10% among COVID-19 patients with DM. It also notified that the mortality and requirement for mechanical ventilation were higher for the patients with newly diagnosed DM in comparison with patients who had DM before admission18 . Meta-analysis from Wu et al, found significant relation of mortality inCOVID-19 patients with pre-existing diabetes, OR of 1.75 (95% CI 1.31-2.36; P=0.0002)…”
mentioning
confidence: 99%
“…The prevalences of DM and prediabetes in the GCC countries varied between 7.6% to 66.4% among hospitalized COVID-19 patients in Saudi Arabia 14 and the UAE, 15 respectively. The coexistence of DM and COVID-19 was associated with worse outcomes and higher mortality rates.…”
mentioning
confidence: 97%